Learning Media, Pop Up Book, Int MEDIA PEMBELAJARAN POP UP BOOK DENGAN TEKNIK INTERNAL STAND UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK KELAS IV SD : penelitian pengembangan media pembelajaran - fajarmaulana; Wahyu Kurniawati; Heru Purnomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This”research”was”conducted using the 4D”development”model, which”produced learning media in the form of Pop Up Book with Internal Stand to improve”learning achievement”in the”subject of science and natural sciences. Based on the assessment of media experts, a total score of 91 was obtained, while the science and natural sciences expert gave a total score of 94 out of a maximum total value of 100. If categorized, the results are included in”the 'very”valid' category, the assessment”of teachers in the trial obtained a score of 36 out of a maximum total of 40, which if expressed as a percentage reaches 90% in the range of 81.25%–100, thus indicating the category of "very practical". The”response”of”students”obtained a percentage of 92.5%, which also shows”that this media is”very practical”to apply in research.